Optimalisasi Penggunaan Teknologi Pendidikan dan Kemampuan Literasi Media pada Masa Pandemi Covid-19 - Herlina, Erna; Yusnita, Nancy; Sutrisno, Slamet; Junengsih, Junengsih; Rosyadi, Imam (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The COVID-19 pandemic has brought changes in the world of education that impact dependence on the use of technology in the learning process and increase independent learning that requires learning media literacy skills. The purpose of this study was to review the optimization of the use of technology in education and media literacy skills during the COVID-19 pandemic. This research is a literature review using primary sources from 8 journals published in 2021-2022. The results of the study show that optimizing the use of technology in education during the COVID-19 pandemic can be done by focusing on increasing the utilization, service, and acceptance of this media as a learning tool through increasing perceptions of usability, perceived ease of use, attitudes towards online learning, motivation, mindset and collaboration. ; and aspects of educators such as the attitude of the instructor, competence and interaction of students. The family's socioeconomic status and parents' education level influence are increasing the media literacy skills of students who can support distance learning during the COVID-19 pandemic.